Incidence of Long Bone Fractures in Goat and Sheep – A Study Report - Sindhu, R; Puli Vishnu Vardhan Reddy; Saran, S (The Indian Veterinary Journal, 2024)
Fractures of long bones are the major common orthopaedic conditions encountered in goats and sheep. A total of 92 goats and 6 sheep long bone fracture cases were recorded for the period January 2022 to February 2023 in which highest incidence was noted in male animals below 6 months of age. Metacarpal bone accounted for the highest incidence of fractures 26.08%, followed by femur 21.7%, tibia and fibula 14.1%, radius and ulna 14.1% and metatarsal 14.1%. Oblique fractures noted 40.21% of all, followed by transverse fractures 36.95%, and multiple fractures 22.82%.